Estimativa da altura por dimensões dentárias: uma revisão da literatura - Herrera, Lara Maria [UNESP]; Serra, Mônica da Costa [UNESP]; Fernandes, Clemente Maia da Silva [UNESP] (My University, 2014)
The knowledge of Forensic Anthropology is very importance in cases of identification of human remains. One phase of this process is the study of human height, which can be accomplished with relative ease when intact corpses, complete skeletons or long bones are available. However, the experience of Forensic Dentistry is essential in situations in which there is only information of the skull or of the teeth. The objective of this study was to review in the literature and evaluate works concerning the estimate of the height calculated from dental dimensions. Carrea, in 1920, proposed the estimation of the probable height of an individual by developing formulas for maximum and minimum heights from measurements of the lower central and lateral incisors and canines. The method was used in the case "Josef Mengele", to complement estimates. Tested in the Brazilian population, 70% of match between the actual and the estimated stature were obtained. Using more precise instruments, in the modified method, 96% of correct matching were verified. Recently, a new formula was introduced to estimate height, from measurements of upper teeth, because the technique cannot be used when jaw is not available. The correlation between height and dental dimensions is demonstrated. However, there is still a lack in scientific literature in this field, and further studies are necessary. The estimate of height from dental dimensions can be very useful and important, especially in situations where the complete skeleton it not found, and long bones are not available.

Os conhecimentos de Antropologia Forense são de suma importância em casos de identificação de despojos humanos. Uma das fases desse processo é o estudo da altura, que pode ser realizado com relativa facilidade quando corpos íntegros, esqueletos completos ou ossos longos estiverem disponíveis. No entanto, a experiência do odontolegista é imprescindível em situações deparadas apenas com informações do crânio ou dos dentes. O objetivo deste trabalho foi realizar um levantamento da literatura, e análise dos estudos relativos à estimativa da altura obtida por meio das dimensões dentárias. Carrea, em 1920, possibilitou o cálculo da altura mais provável do indivíduo através da elaboração de fórmulas para alturas máxima e mínima a partir de mensurações dos incisivos central e lateral e caninos inferiores. O método foi utilizado no caso “Josef Mengele”, para complementar estimativas. Testado na população brasileira, foram obtidos 70% de coincidência com a estatura real e a estimada. Com o uso de instrumentos mais precisos, no Método Modificado, 96% de acerto foram encontrados. Recentemente, uma nova fórmula foi apresentada para estimar a altura, a partir de medidas de dentes superiores, tendo em vista a impossibilidade da aplicação da técnica quando a mandíbula não está à disposição. A correlação entre altura e dimensões dentárias está demonstrada. Entretanto, a literatura científica ainda é carente de trabalhos nesta seara, e novas pesquisas fazem-se necessárias. A estimativa da altura a partir das dimensões dentárias pode ser muito útil e importante, sobretudo em situações em que não é encontrado o esqueleto completo, e faltam os ossos longos.
Stature estimation from dental dimensions: a literature review
Keywords: Forensic dentistry; Forensic anthropology; Human identification; Body height; Odontologia legal; Antropologia forense; Identificação humana; Estimativa da altura